Inherent resistivity of graphene to strong THz fields - Turchinovich, Dmitry; Mics, Zoltan; Jensen, Soren; Parvez, Khaled; Ivanov, Ivan; Tielrooij, Klaas-Jan; Koppens, Frank H. L.; Feng, Xinliang; Muellen, Klaus; Bonn, Mischa (Springer Proceedings in Physics, 2015)
The THz conductivity of graphene at high driving THz fields was characterized using nonlinear ultrafast THz spectroscopy. We found that efficient carrier heating by strong THz signals leads to increased effective carrier scattering time. However, counter-intuitively, the heating also results in reduced high-frequency conductivity.
CRIS-Team Scopus Importer:2023-03-20